Analysis of Poetry Reading Skills in Kartini Young Literature - Yerry Mijianti; Muhammad Noor Ahsin; Dwi Setiyawan; Ramadhan Kusuma Yudha; Sarwiji Suwandi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Kartini Muda activity in literature is a poetry reading activity held by Hima PBSI FKIP Muria Kudus University which was attended by seventeen high school students in Pati Residency, Central Java Province. The background of this research is that there are many literary activities or poetry reading competitions held by institutions or communities in the community, but not many analyze and describe the poetry skills of the participants in detail. Even though the analysis and description are important to be known by participants, the community, teachers, and also students because they can be used as references for poetry reading assessments. The purpose of this study is to describe poetry reading skills in young Kartini videos with literature. This research is a qualitative descriptive study. The data used are poetry reading videos sent by participants. The results showed that reading poetry in the Kartini Muda Bersastra activity in terms of appreciation, expression, pronunciation, intonation, and appearance were very good, good, adequate, and lacking; while for the appearance of all students have shown a pretty good poetry reading.